The military covenant its impact on civil-military relations in Britain - Ingham, Sarah (Ashgate Publishing Ltd, 2014)
The Military Covenant states that in exchange for their military service and their willingness to make the ultimate sacrifice, soldiers should receive the nation's support. Exploring the concept's invention by the Army in the late 1990s, its migration to the civilian sphere from 2006 and its subsequent entrenchment in public policy